2015
DOI: 10.3762/bjoc.11.3
|View full text |Cite
|
Sign up to set email alerts
|

Three-component synthesis of C2F5-substituted pyrazoles from C2F5CH2NH2·HCl, NaNO2 and electron-deficient alkynes

Abstract: SummaryA one-pot reaction between C2F5CH2NH2·HCl, NaNO2 and electron-deficient alkynes gives C2F5-substituted pyrazoles in excellent yields. The transformation smoothly proceeds in dichloromethane/water, tolerates the presence of air, and requires no purification of products by column chromatography. Mechanistically, C2F5CH2NH2·HCl and NaNO2 react first in water to generate C2F5CHN2, that participates in a [3 + 2] cycloaddition with electron-deficient alkynes in dichloromethane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 51 publications
1
14
0
Order By: Relevance
“…The same regularity was observed in the case of highly reactive bromonitrile oxide, yet the yield of target isoxazole 20 k was high (entry 11). As expected, isoxazoles derived from the low stable aliphatic nitrile oxides were formed in moderate to low yields (entries 8,9); in the reaction of HFB with hydroximinoyl chloride 14 l the target isoxazole was not observed in the reaction mixture (entry 12). Finally, highly reactive trifluoroacetonitrile oxide did not add to HFB and gave only dimers -furoxan and dioxadiazine [26] as evidenced by the 19 F NMR data (entry 13).…”
Section: Entrysupporting
confidence: 61%
See 2 more Smart Citations
“…The same regularity was observed in the case of highly reactive bromonitrile oxide, yet the yield of target isoxazole 20 k was high (entry 11). As expected, isoxazoles derived from the low stable aliphatic nitrile oxides were formed in moderate to low yields (entries 8,9); in the reaction of HFB with hydroximinoyl chloride 14 l the target isoxazole was not observed in the reaction mixture (entry 12). Finally, highly reactive trifluoroacetonitrile oxide did not add to HFB and gave only dimers -furoxan and dioxadiazine [26] as evidenced by the 19 F NMR data (entry 13).…”
Section: Entrysupporting
confidence: 61%
“…Recently the same pyrazole has been obtained via cycloaddition of HFB to easily available ethyl 2‐diazo‐3,3,3‐trifluoropropanoate . A perfluoroalkylated pyrazole with one C 2 F 5 and two CF 3 groups was formed under interaction of pentafluorodiazopropane and HFB . Hartman and Regitz carried out the reaction of HFB with phosphoryldiazomethane and obtained N ‐phosphorylpyrazole, which was hydrolised to the appropriate 1 H ‐pyrazole with two CF 3 groups .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[63] In entry b, Rack et al found that the trifluoromethyl enone shown underwent reductive defluorination before condensing with methylhydrazine to produce a 94:6 ratio of pyrazoles 71:72 in 70 % yield. [66,67] Ma and co-workers have developed a method of obtaining highly regioselective 3-substituted (trifluoromethyl)pyrazoles via silver-mediated cycloaddition of alkynes. [65] Finally, Touzot's team reacted the diethylenaminone in entry d with methylhydrazine under mild conditions to give a 2.5:1 ratio of pyrazoles 71:72 in yields ranging from 80-91 %.…”
Section: Regioselective 3-r F -(-Ar F )-Pyrazole Ring Preparationsmentioning
confidence: 99%
“…With the advent of safe and selective fluorinating agents and rapid development of the synthesis methodology of asymmetric fluorination [57,58], there is still great scope for the exploitation of compounds featuring a fluorine atom on (or around) a suitable stereocenter in the key pharmacophoric site of promising NNRTI scaffolds. …”
Section: Expert Opinionmentioning
confidence: 99%